The Pax Assyriaca : the historical evolution of civilisations and the archaeology of empires - Toro, Benjamin (Archaeopress Archaeology, 2022)
This volume provides a study of the evolutionary process of ancient civilisations, stressing the comparison between theoretical principles and relevant historical and archaeological evidence. For this reason, the study focuses on the origin, development and collapse of the first stage of the 'Central Civilization', which was the result of the merger of two primeval civilisations, Mesopotamia and Egypt, during the 'Near Eastern phase' of this Central Civilisation. This merger seems to have been the result of the political expansion of an imperial entity coming from Mesopotamia under the aegis of the so-called Neo-Assyrian Empire from 1000 BC to 600 BC - better known as the Pax Assyriaca - although the process of full integration with Egypt seems to have been concluded, according to the archaeological records, only by the successor empires of Assyria circa 430 BC.